New garlic variety Agrifound Parvati 2 - Singh, R K; Dubey, B K; Gupta, R P (Indian Horticulture, 2015)
Garlic Agrifound Parvati 2 is a new variety for mid and higher hills and popular among farmers for higher yield with better adaptability. The variety is a long day type and recommended for the cultivation in Jammu Kashmir and Himachal Pradesh.